KEHADIRAN MOTIF CERITA MADAME BOVARY (1856) KARYA GUSTAVE FLAUBERT DALAM HIKAYAT SITI MARIAH (1910--1912) KARYA HADJI MOEKTI: KAJIAN SASTRA BANDINGAN - Susanto, Dwi (Widyaparwa, 2023)
The presence of Madame Bovary's story motif (1856) in Indonesian literature, especially Hikayat Siti Mariah (1910--1912) provides evidence that there is a reception of similar between French and Dutch colonial or Indonesian. This paper aims to (1) find out the ideas of the two texts in displaying similar story motif, (2) the form of respons from Madame Bovary (1856) in the Hikayat Siti Mariah (1910--1912), and (3) the significance of Madame Bovary's presence (1856) in the Hikayat Siti Mariah (1910--1912) as a social response. This paper uses a comparative literary point of view by considering the social context as a response. The objects are Madame Bovary (1856) by Gustave Flaubert and Hikayat Siti Mariah (1910--1912) by Hadji Moekti and the significance of the presence of Madame Bovary in Indonesian literature. The research data consists of the content or ideas of the two texts, the spirit of age, and the social context. Data interpretation is done by comparing the content or ideas of the two texts by considering the social context of each text. The results obtained are (1) the two texts present ideas against the bourgeois class resistance by using symbols of women and sexuality, (2) the Hikayat Siti Mariah (1910--1912) takes the motive of the story to attack the Dutch capitalists and liberal groups who construct the identities of the colonized subjects, and (3) the presence of the text of Madame Bovary (1856) in Indonesian literature shows a global anti-colonial spirit. Kehadiran motif cerita Madame Bovary (1856) dalam sastra Indonesia terutama Hikayat Siti Mariah (1910--1912) memberikan bukti terdapat resepsi atas semangat dan persoalan yang serupa antara masyarakat Prancis dan tanah jajahan Belanda atau Indonesia. Tulisan ini bertujuan untuk (1) mengetahui gagasan kedua teks tersebut dalam menampilkan motif cerita yang serupa, (2) mengetahui wujud sambutan dari Madame Bovary (1856) dalam teks Hikayat Siti Mariah (1910--1912), dan (3) mengetahui makna kehadiran Madame Bovary (1856) dalam teks Hikayat Siti Mariah (1910--1912) sebagai satu respon sosial. Tulisan ini mengunakan sudut pandang sastra bandingan dengan mempertimbangkan konteks sosial sebagai satu respon. Objek tulisan ini adalah Madame Bovary (1856) karya Gustave Flaubert dan Hikayat Siti Mariah (1910--1912) karya Hadji Moekti dan  makna kehadiran teks Madame Bovary dalam sastra Indonesia. Data penelitian ini terdiri atas isi atau gagasan dari kedua teks, semangat zaman, dan konteks sosial. Interpretasi data dilakukan dengan membandingkan isi atau gagasan kedua teks dengan mempertimbangkan konteks sosial masing-masing teks. Hasil yang diperoleh adalah (1) kedua teks menghadirkan gagasan terhadap perlawanan kelas borjuis dengan memanfaatkan simbol perempuan dan seksualitas, (2) teks Hikayat Siti Mariah (1910--1912) mengambil motif cerita untuk menyerang kaum kapitalis dan golongan liberal Belanda yang mengkonstruksi identitas  subjek terjajah, dan (3) kehadiran teks Madame Bovary (1856) dalam sastra Indonesia menunjukan semangat anti penjajahan yang mengglobal terutama kolonialisme.